2022
DOI: 10.1177/09544097221089389
|View full text |Cite
|
Sign up to set email alerts
|

A review on cybersecurity in railways

Abstract: Digitalisation is transforming the railway globally. One of the major considerations in digital transformation of any industry including the railway is the increased exposure to cyberattacks. The railway industry is vulnerable to these attacks because since the number of digital items and also number of interfaces between digital and physical components in the railway systems keep increasing. Increased number of items and interfaces require new frameworks, concepts and architectures to ensure the railway syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…Similarly, Özsungur [ 93 ] researched business strategy for cybersecurity in digital transformation, and Nguyen Duc [ 94 ] documented security risk from an engineering perspective. Furthermore, Hai et al [ 1 ] highlighted the opportunities and challenges for emerging countries regarding digital transformation, and Kour’s work [ 95 ] focused on cybersecurity implications in the railway domain. Despite these surveys within the literature, no survey has presented a domain taxonomy and looked into cybersecurity implications in diverse industries, as has been explored in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Özsungur [ 93 ] researched business strategy for cybersecurity in digital transformation, and Nguyen Duc [ 94 ] documented security risk from an engineering perspective. Furthermore, Hai et al [ 1 ] highlighted the opportunities and challenges for emerging countries regarding digital transformation, and Kour’s work [ 95 ] focused on cybersecurity implications in the railway domain. Despite these surveys within the literature, no survey has presented a domain taxonomy and looked into cybersecurity implications in diverse industries, as has been explored in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Özsungur [93] researched business strategy for cybersecurity in digital transformation, and Nguyen Duc [94] documented security risk from an engineering perspective. Furthermore, Hai et al [1] highlighted the opportunities and challenges for emerging countries regarding digital transformation, and Kour's work [95] focused on cybersecurity implications in the railway domain. Despite these surveys within the literature, no survey has In the literature, some review articles have focused on digital transformation, such as an article by Metawa et al [92], which investigated the role of information in digital transformation in the context of Egyptian small-and medium-scale enterprises.…”
Section: Discussionmentioning
confidence: 99%
“…However, with regard to communication, cybersecurity seems to be a future key aspect to be developed. Reference [207] presented a systematic review and outlined emerging trends and approaches in cybersecurity. Possible solutions were identified by consulting the literature, academia, and industry for future directions.…”
Section: Future Researchmentioning
confidence: 99%
“…Although there are many novel state-of-the-art security-enhancing features and frameworks, one of the research gaps in railway security, as identified by the recent review paper on the subject [ 17 ], is the lack of experimental validation. While some works include experimental data, they are often extracted out of a software simulation, whose behavior might deviate from real-world scenarios.…”
Section: Introductionmentioning
confidence: 99%